2019
DOI: 10.1140/epja/i2019-12718-2
|View full text |Cite
|
Sign up to set email alerts
|

Precision resonance energy scans with the PANDA experiment at FAIR

Abstract: This paper summarises a comprehensive Monte Carlo simulation study for precision resonance energy scan measurements. Apart from the proof of principle for natural width and line shape measurements of very narrow resonances with PANDA, the achievable sensitivities are quantified for the concrete example of the charmonium-like X(3872) state discussed to be exotic, and for a larger parameter space of various assumed signal cross-sections, input widths and luminosity combinations. PANDA is the only experiment that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…energy tuned to measure the line shape between 4010 and 4020 MeV, a high precision measurement of the X(3872) binding energy is foreseen at PANDA which has a brilliant energy resolution. Together with the possible high-precision measurements of (the upper limit of) the X(3872) width at PANDA [365] and Belle-II [366], a deeper understanding of the puzzling X(3872) is foreseen.…”
Section: Xy Z Statesmentioning
confidence: 99%
“…energy tuned to measure the line shape between 4010 and 4020 MeV, a high precision measurement of the X(3872) binding energy is foreseen at PANDA which has a brilliant energy resolution. Together with the possible high-precision measurements of (the upper limit of) the X(3872) width at PANDA [365] and Belle-II [366], a deeper understanding of the puzzling X(3872) is foreseen.…”
Section: Xy Z Statesmentioning
confidence: 99%
“…[24] it was found that light scalar tetraquarks mainly depend on the three variables encoded in S 0 and D. Retaining S 0 only, their masses are in the ballpark of what one would naively expect for a state made of four quarks (∼ 1500 MeV for four light quarks). However, the four-quark BSE dynamically and self-consistently generates intermediate meson-meson and dq-dq poles in the dressing functions f i corresponding to the (12)(34), (13) (24) and (14)(23) topologies. These poles appear in the Mandelstam plane formed by the doublet variables D and produce decay thresholds.…”
Section: B Four-quark Amplitudementioning
confidence: 99%
“…the so-called X,Y,Z states, like the X(3872) state [3] or the P c pentaquark candidates [4]. More exciting experimental data are expected from the B-factories Belle II [5] and BESIII [6], the LHCb experiment [7], the PANDA experiment at FAIR [8] and at a future Super-c-τ Factory [9].…”
Section: Introductionmentioning
confidence: 99%